Molecular identification of evolutionary significant units in the Amazon river dolphin Inia sp. (Cetacea: Iniidae) - Banguera Hinestroza, E; Cárdenas, H.; Ruíz Garcia, M; Marmontel, M; Gaitán Solís, Eliana; Vázquez, R.; García Vallejo, F. (Oxford University Press, 2002)
The Amazon river dolphin, genus Inia, is endemic to the major river basins of northern South America. No previous studies have focused on the genetic structure of this genus. In this work, 96 DNA samples from specimens of this genus were collected in the Orinoco basin (four rivers), the Putumayo River, a tributary of the Colombian Amazon and the Mamoré, and the Tijamuchí and Ipurupuru rivers in theBolivian Amazon. These samples were used to amplify a fragment of 400 bp of the mitochondrial DNA (mtDNA) control region. In addition, 38 of these samples were also used to sequence 600 bp of the mitochondrial cytochrome b gene. The analysis of the population structure subdivision with an analysis of molecular variance (AMOVA) revealed important aspects about the genetic structure of Inia groups fromthese three geographically separate regions. By comparing the control region DNA and cytochrome b sequences, distinct types of nonshared haplotypes were observed. The net genetic divergence of control region sequences was 6.53% between the Orinoco and Bolivian rivers, 5.32% between the Putumayo and Bolivian rivers, and 2.50% between the Orinoco and Putumayo rivers. For the cytochrome b gene, these values were 2.48%, 2.98%, and 0.06%, respectively. The nucleotide sequences were analyzed phylogenetically using several genetic distance matrices and applying neighbor-joining, maximum likelihood, and maximum parsimony procedures. The results support the proposal to subdivide the Inia genus into at least two evolutionarily significant units: one confined to the Bolivian river basin and the other widely distributed across the Amazon and Orinoco basins.